Wiener measure on pe(g) (1997)
Nonstandard methods allow a flat integral representation of de Wiener measure on Po (R). A representation of the Wiener measure on Po (Rd) is given, allowing us to give a nonstandard representation of the Wiener measure on Pe (G) by using Ito raap